Penerapan Media Audio Visual dalam Meningkatkan Hasil Belajar Siswa Madrasah Ibtidaiyah - Yulizar, Ismi; Yuni, Yuli; Putri, Dwina; Ritonga, Ali Sadikin; Sinaga, Elviana; Ansori, Ahmad (Dawuh Guru: Jurnal Pendidikan MI/SD, 2024)
This classroom action research aims to improve student learning outcomes in social studies for fifth-grade students at MIS Harisma Pulo Padang through the implementation of audio-visual media. The researcher involved 11 students in two systematically designed learning cycles. In the first cycle, audio-visual media was introduced to the students to provide a basic understanding of the material being taught. In the second cycle, the use of audio-visual media was reinforced to optimize its application and solidify student comprehension. Learning outcome data were collected through pre-tests and post-tests, as well as structured classroom observations. The research results indicate that the implementation of audio-visual media has a significant impact on improving student achievement in social studies. Data analysis from the first cycle showed that 64% of students achieved the passing criteria, while 36% did not. However, after reinforcing the use of audio-visual media in the second cycle, the percentage of students meeting the passing criteria increased significantly to 91%, with only 9% not achieving the criteria. This significant improvement demonstrates that the use of audio-visual media is highly effective in enhancing the learning outcomes of fifth-grade students at MIS Harisma Pulo Padang. Therefore, this research contributes to the development of more interactive and effective teaching methods, particularly in social studies, and it is hoped that these methods can be more widely implemented in other schools.